2015
DOI: 10.3390/ph8010107
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of the Impact of 21-Gene Recurrence Score Assay on Treatment Choice in Node Positive Micrometastatic Breast Cancer

Abstract: To assess clinical utility of the 21-gene assay (Oncotype DX® Recurrence Score®), we determined whether women with HER2(−)/ER+ pN1mi breast cancer with low (<18) Recurrence Scores results are given adjuvant chemotherapy in a lower proportion than those with high scores (≥31). This was a multicenter chart review of ≥18 year old women with pN1mi breast cancer, HER2(−)/ER+ tumors, ductal/lobular/mixed histology, with the assay ordered on or after 1 January 2007. One hundred and eighty one patients had a mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…In addition to local therapy, systemic treatments can modify the survival outcomes of patients. Biologic factors including breast cancer subtype and multigene assay score have consistently been associated with treatment decisions and outcomes for patients with pN1mi disease [27, 28]. Our subgroup analyses also presented advantages of chemotherapy in patients with the non‐luminal A‐like subtype and node‐positive disease.…”
Section: Discussionmentioning
confidence: 82%
“…In addition to local therapy, systemic treatments can modify the survival outcomes of patients. Biologic factors including breast cancer subtype and multigene assay score have consistently been associated with treatment decisions and outcomes for patients with pN1mi disease [27, 28]. Our subgroup analyses also presented advantages of chemotherapy in patients with the non‐luminal A‐like subtype and node‐positive disease.…”
Section: Discussionmentioning
confidence: 82%
“…Another multicenter chart review of patients with estrogen receptor-positive and HER2-negative pN1mi breast cancer found that despite this limited data, clinical practice differed by recurrence score: most patients with low recurrence scores (defined by that study as RS < 18) were recommended endocrine monotherapy (80.2%), while the majority of patients (77.0%) with RS ≥ 31 were recommended combined endocrine and chemotherapy ( P < .001). 12 Because the publication of that study, clinical consensus on pertinent RS cutoffs has evolved, and our study uses updated 21-gene recurrence score cutoffs based on the TAILORx trial to confirm that treatment practices for patients with RS < 26 differ by lymph node status. In our analysis of patients with RS < 26, we found that despite this low-risk stratification by ODX, combined chemo-endocrine therapy was used 2-fold more frequently in patients with pN1mi compared to pN0, yet not as often as in patients with pN1a-c disease.…”
Section: Discussionmentioning
confidence: 99%
“…The 21-gene RS assay is also recommended in patients with N1mi disease. However, limited studies are available to assess whether the 21-gene RS results are useful in guiding decisions regarding chemotherapy beyond standard clinicopathologic characteristics [15]. In light of this, we performed a population-based study to assess the predictive and prognostic value of the 21-gene RS assay on decision for chemotherapy in N1mi patients.…”
Section: Introductionmentioning
confidence: 99%